Loss of insulin signaling in microglia impairs cellular uptake of Aβ and neuroinflammatory response exacerbating AD-like neuropathology - Wenqiang Chen; Xiangyu Liu; Vitor Rosetto Muñoz; C. Ronald Kahn (Proceedings of the National Academy of Sciences, 2025)
Insulin receptors are present on cells throughout the body, including the brain. Dysregulation of insulin signaling in neurons and astrocytes has been implicated in altered mood, cognition, and the pathogenesis of Alzheimer’s disease (AD). To define the role of insulin signaling in microglia, the primary phagocytes in the brain critical for maintenance and damage repair, we created mice with an inducible microglia-specific insulin receptor knockout (MG-IRKO). RiboTag profiling of microglial mRNAs revealed that loss of insulin signaling results in alterations of gene expression in pathways related to innate immunity and cellular metabolism. In vitro, loss of insulin signaling in microglia results in metabolic reprogramming with an increase in glycolysis and impaired uptake of Aβ. In vivo, MG-IRKO mice exhibit alterations in mood and social behavior, and when crossed with the 5xFAD mouse model of AD, the resultant mice exhibit increased levels of Aβ plaque and elevated neuroinflammation. Thus, insulin signaling in microglia plays a key role in microglial cellular metabolism and the ability of the cells to take up Aβ, such that reduced insulin signaling in microglia alters mood and social behavior and accelerates AD pathogenesis. Together, these data indicate key roles of insulin action in microglia and the potential of targeting insulin signaling in microglia in treatment of AD.